2011
DOI: 10.1002/lary.21894
|View full text |Cite
|
Sign up to set email alerts
|

Cervical variations of the phrenic nerve

Abstract: The present study demonstrates the wide variability within the cervical anatomy of the phrenic nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…However, a single phrenic nerve arising from C4 with contributions of C3 and C5 roots is only found in 22% of cadavers. Sometimes there are contributions of only 1 or 2 of these 3 roots . Accessory and secondary phrenic nerves joining the main phrenic nerve before or after entering the thoracic cavity were found in 48.5%.…”
Section: Discussionmentioning
confidence: 99%
“…However, a single phrenic nerve arising from C4 with contributions of C3 and C5 roots is only found in 22% of cadavers. Sometimes there are contributions of only 1 or 2 of these 3 roots . Accessory and secondary phrenic nerves joining the main phrenic nerve before or after entering the thoracic cavity were found in 48.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The right nerve originated from C5 alone, while in the left, the nerve originated from supraclavicular nerve and C5. Mendelsohn, Deconde, Lambert et al (2011) studied the variations of the phrenic nerve (sample size 110 cadaver). Their study showed the most common pattern of the phrenic nerve consists of phrenic nerve with single C3 and C4 rootles with an immeasurable C5 which was present in 26% of the necks.…”
Section: Discussionmentioning
confidence: 99%
“…It descends between fibrous pericardium and mediastinal parietal pleura, supplying pericardium, pleura and diaphragm (BERGMAN, THOMPSON, AFIFI et al, 1988). The anatomical variations of the phrenic nerve is of great importance due to possible complete paralysis of diaphragm particularly in patients undergoing supraclavicular block (MENDELSOHN, DECONDE, LAMBERT et al, 2011). Furthermore a thorough knowledge of the cervical variations of the phrenic nerve could be worthwhile in restorative surgeries in neck region (BIGELEISEN, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Its occurrence in cadaveric studies was thought to be 61.8% to 65% (Kelley 1950). Other authors have reported the incidence to be as low as 3% (Dayal & Ky 2009) with a 5% incidence of cadavers displaying an accessory phrenic nerve (Mendelsohn et al 2011). Figure 4 Anatomical location of the brachial plexus (Gray 1918) In a review by Prates J unior, any nerve that had contributions to the phrenic nerve was classed as an accessory phrenic nerve.…”
Section: Anatomical Variationmentioning
confidence: 99%